11β-hydroxylase deficiency caused by a novel CYP11B1 variant: A case report - Hossam A Aldosari; Rawand N Alharbi (Wolters Kluwer Medknow Publications, 2023)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders of adrenal steroid biosynthesis. 11β-hydroxylase deficiency (11 β-OHD) - caused by a mutation in CYP11B1 - is responsible for 5%-8% of all CAH cases. In the classic form, genotypic female newborns exhibit ambiguous genitalia, but the disorder can remain undetected in males. We report a 2-year, 8-month-old male patient with 11 β-OHD presenting with pseudoprecocious puberty, hypertension, and skin hyperpigmentation. His biochemical profile revealed elevated basal 11-deoxycorticosterone (DOC) and corticotropin levels. The diagnosis was confirmed by detecting a novel splicing mutation in CYP11B1 (NM_000497.3) (c. 955-1G>C). The patient was prescribed hydrocortisone and leuprolide acetate treatment and follow-up appointments. His blood pressure, 11-DOC levels, and skin hyperpigmentation improved after treatment. No further changes in pubertal development were noted. This splicing variant has not been previously reported; hence, our findings broaden the spectrum of the existing database of pathogenic CYP11B1 mutations.